2021
DOI: 10.1021/acscatal.1c03988
|View full text |Cite
|
Sign up to set email alerts
|

Gating of Substrate Access and Long-Range Proton Transfer in Escherichia coli Nitrate Reductase A: The Essential Role of a Remote Glutamate Residue

Abstract: The Mo/W-bisPGD enzyme superfamily comprises a vast number of mononuclear molybdenum and tungsten enzymes that catalyze a great diversity of vital reactions in prokaryotes. In the past decades, much attention has been devoted to the immediate surroundings of the metal atom highlighting the importance of the inner coordination sphere but have failed to identify molecular determinants of the reactivity. Here, we report the mechanistic importance of a set of conserved residues that line the substrate entry tunnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…Such small conformational changes may result from distant structural influences induced either by the activation process or by the nature of the reductant. Indeed, it has been recently shown that in the closely related Mo-enzyme, respiratory nitrate reductase, some modifications of the H-bond network in the substrate access tunnel can remotely affect the spectroscopic and redox properties of the Mo cofactor . Although there is no structural difference in the substrate access tunnel in the fully reduced enzyme (W IV ) either by dithionite or formate, similar effects are potentially at work in the intermediate W V redox state of FdhAB in solution.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such small conformational changes may result from distant structural influences induced either by the activation process or by the nature of the reductant. Indeed, it has been recently shown that in the closely related Mo-enzyme, respiratory nitrate reductase, some modifications of the H-bond network in the substrate access tunnel can remotely affect the spectroscopic and redox properties of the Mo cofactor . Although there is no structural difference in the substrate access tunnel in the fully reduced enzyme (W IV ) either by dithionite or formate, similar effects are potentially at work in the intermediate W V redox state of FdhAB in solution.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Indeed, it has been recently shown that in the closely related Mo-enzyme, respiratory nitrate reductase, some modifications of the H-bond network in the substrate access tunnel can remotely affect the spectroscopic and redox properties of the Mo cofactor. 48 Although there is no structural difference in the substrate access tunnel in the fully reduced enzyme (W IV ) either by dithionite or formate, similar effects are potentially at work in the intermediate W V redox state of FdhAB in solution. The striking conversion of the W F V species into W D V upon dithionite addition might be explained by an indirect effect of dithionite on the H-bond network in the metal cofactor surrounding or in the substrate access tunnel.…”
Section: Results and Discussionmentioning
confidence: 99%
“…67 Besides, there are some interesting examples of redesigning tunnels. Researchers have successfully changed the size, shape, and other properties of the tunnel by altering some local structures that are closely related to the entry tunnel, such as loops, C-terminals, and hydrogen bonds, to affect the conformation of the enzyme 33,47,106 (Figure 7D). Yang et al found that the 33 amino acid residues at the C-terminals of Lactobacillus plantarum phytase (LpPHY) are mostly amino acids with small and relatively flexible side chain groups, such as alanine and glycine, which are usually removed to improve protein expression efficiency when they appear at the end of the protein.…”
Section: Directed Evolution Of Tunnelmentioning
confidence: 99%
“…Considering the special role of the tunnel, lipase biocatalysis and biotransformation can be greatly improved by reconstructing the tunnel from the molecular and catalytic characteristics of lipase. In the past few years, a number of publications have focused on the design of substrate tunnels and have yielded a number of enzymes with excellent performance. , Therefore, rational design of the lipase tunnel precisely regulates the transport rate of water and accelerates the progress of the enzymatic esterification reaction, thus improving the efficiency of the enzymatic reaction. This work will help to solve the key scientific problem of “substrates and products passage” in enzymatic esterification systems and provide ideas to break the bottleneck in the application of esterification in industry.…”
Section: Lipase Utilized As a Unique And Powerful Biocatalystmentioning
confidence: 99%
“…The aquo ligand is bound only weakly and its dissociation generates a coordinatively unsaturated Mo center that binds an oxygen atom from a nitrate anion and initiates its reduction to a nitrite anion via an oxygen atom transfer to Mo IV . [11][12] Subsequently, the sixelectron reduction of a nitrite anion to an ammonium cation can be catalyzed by cytochrome c nitrite reductase (NrfA) enzymes. [13] The active site in those enzymes is an Fe heme site coordinated by an amine group of lysine in the proximal axial position, while the distal axial coordination site is free to interact with substrates such as nitrite and hydroxylamine species.…”
Section: Introductionmentioning
confidence: 99%